A New Heuristic Approach for Low-Thrust Spacecraft Trajectory Optimization1Peter Coppens' and Panagiotis Patrinos' research is supported by the Fonds Wetenschappelijk Onderzoek PhD grant 11E5520N and research projects G0A0920N, G086518N and G086318N; Research Council KU Leuven C1 project No. C14/18/068; Fonds de la Recherche Scientifque – FNRS and the Fonds Wetenschappelijk Onderzoek – Vlaanderen under EOS project no 30468160 (SeLMA). Ben Hermans' and Goele Pipeleers' research benefts from KU Leuven-BOF No. PFV/10/002, from project No. G0C4515N of the Research Foundation - Flanders (FWO - Flanders), from Flanders Make ICON: Avoidance of collisions and obstacles in narrow lanes, and from the KU Leuven Research project No. C14/15/067. Issue 2 (2020) - Coppens, Peter; Hermans, Ben; Vandersteen, Jeroen; Pipeleers, Goele; Patrinos, Panagiotis
Abstract: Electrical propulsion is gaining popularity in the satellite industry. Their high efficiency however comes at the cost of decreased thrust and longer transfer times. As such the interest in solving the large optimization problems associated with these long transfers has re-surged. This paper presents a heuristic approach to solving such low-thrust satellite trajectory optimization problems, based on control law blending and averaging. We derive the nonlinear program resulting from this approach and introduce PANOC, a recent optimization algorithm well suited for optimal control problems. The resulting controller is considerably faster than more classical, non-heuristic approaches, without a significant loss in optimality.